High anti-collagen type-II antibody levels and induction of proinflammatory cytokines by anti-collagen antibody-containing immune complexes in vitro characterise a distinct rheumatoid arthritis phenotype associated with acute inflammation at the time of disease onset. Issue 4 (13th October 2006) - Mullazehi, Mohammed; Mathsson, Linda; Lampa, Jon; Rönnelid, Johan
Abstract : Objective: To investigate whether the cytokine-inducing properties of surface-bound collagen type II (CII)-containing immune complexes (IC), which were reported earlier, have any clinical impact. Methods: Anti-CII serology was analysed in 274 patients with early rheumatoid arthritis (RA). Patients with increased levels of anti-CII were followed serially for 1–5 years with regard to anti-CII IC-induced levels of tumour necrosis factor (TNF)α, interleukin (IL)1β and IL8. Levels of antibodies and IC-induced cytokines were compared with clinical indices over 5 years of follow-up. Results: 5/100 healthy controls and 24/274 (8.8%) patients with RA exhibited increased levels (>29 arbitrary units (AU)/ml) of anti-native CII antibodies, a non-significant difference. 9/274 (3.3%) patients with RA and no controls comprised a discrete group with high anti-CII levels >450 AU/ml. These high anti-CII level sera were associated with induction of pro-inflammatory cytokines by anti-CII-containing IC formed in vitro. 8/9 patients with high baseline anti-CII levels exhibited a parallel decline in antibody levels, IC-induced cytokines, C reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Anti-CII-positive patients had significantly increased levels of CRP and ESR at baseline, but not later during the follow-up. Conclusions: Anti-native CII-positive patients with RA have a distinct clinical phenotype characterised by an early acute phase response that might be driven by anti-CII-containing IC in joint cartilage.